Dark breaks the dawn - Larson, Sara B. (Larson, Sara B. Dark breaks the dawn (Series), 2017)
Princess Evelayn, eighteen, of Éadrolan must rely on her newly acquired magical powers as war between the Light Kingdom and the Dark Kingdom rages.